How Real Is Climate Change? Public Perception in Central Asia, Caucasus Region and Eastern Europe - Aziza Artikova; Bekhzod Egamberdiev; Imomjon Khamidov; Abdulla Primov (ZBW - Leibniz Information Centre for Economics, 2025)
The development of appropriate climate change makes people perceive it in a certain way, and is critical to formulating appropriate environmental policies and environmental education campaigns. In this article, the authors discuss the perception of climate change in four Central Asian countries — namely, the Kyrgyz Republic, Kazakhstan, Tajikistan, and Uzbekistan —as well as the Caucasus region and Eastern Europe.
Keywords: Q54; Q56; P48; 330; Climate change; Perception; Central Asia; Eastern Europe and Caucasus